Representation of Auditory Space by Cortical Neurons in Awake Cats - Mickey, Brian J. (J Neurosci, 2003)
We evaluated the spatial selectivity of auditory cortical neurons in awake cats. Single- and multiunit activity was recorded in primary auditory cortex as the animals performed a nonspatial auditory discrimination or sat idly. Their heads were unrestrained, and head position was tracked. Broadband sounds were delivered from locations throughout 360° on the horizontal plane, and source locations were expressed in head-centered coordinates. As in anesthetized animals, the firing rates of most units were modulated by sound location, and most units responded best to sounds in the contralateral hemifield. Tuning was sharper than in anesthetized cats, in part because of suppression at nonoptimal locations. Nonetheless, spatial receptive fields typically spanned 150-180°. Units exhibited diverse temporal response patterns that often depended on sound location. An information-theoretic analysis showed that information transmission was reduced by ∼10% when the precision of spike timing was disrupted by 16-32 msec, and by ∼50% when all location-related variation of spike timing was removed. Spikes occurring within 60 msec of stimulus onset transmitted the most location-related information, but later spikes also carried information. The amount of information transmitted by ensembles of units increased with the number of units, indicating some degree of mutual independence in the spatial information transmitted by various units. Spatial tuning and information transmission were changed little by an increase in sound level of 20-30 dB. For the vast majority of units, receptive fields showed no significant change with the cat's head position or level of participation in the auditory task.